IT Based Innovation in Rural and Urban WSS : Sanitation Hackathon, Nov. 30-Dec. 2, 2012 - World Bank (Washington, DC, 2014)
The need for innovative solutions to the chronic lack of sanitation worldwide is immense. Of those people who lack access to improved sanitation. 1.1 billion have no facilities at all and defecate in the open. These sanitation shortages account for thousands of deaths daily, especially among children. Additionally, poor sanitation costs billions of dollars in economic losses annually, as high as 7 percent of Gross Domestic Product, or GDP in some countries. 'That's billions of dollars that could educate poor children or help build infrastructure - like schools and roads,' said World Bank Group President Jim Yong Kim. Conversely, more than 6 billion people worldwide have access to a mobile phone, including in rural and urban areas in developing countries. The surge in mobile phones in Africa, some 94 percent of urban Africans, for example, are near a GSM signal, is transforming the way people complete daily tasks, from knowing when to sell farm commodities, to finding easier ways to pay bills or send money to family and friends. With ever increasing mobile penetration and falling prices of smart phones, mobile applications provide a platform to address myriad critical issues and an opportunity to solve problems in the developing world.